Estropause, Sex Hormones and Metal Homeostasis in the Mouse Brain - Liu, Tianbing; Bowen, Richard L.; Wilson, Andrea C.; Atwood, Craig S. (Frontiers in Neurology, 2022)
Alterations in brain metal ion homeostasis have been reported with aging and are implicated in the pathogenesis of neurodegenerative diseases. To assess whether age-related changes in hypothalamic-pituitary-gonadal (HPG) hormones might be involved in modulating brain metal ion homeostasis, we treated 7.5-month intact, sham-ovariecomized and ovariectomized C57B6SJL mice with vehicle or leuprolide acetate (for 9-months) to differentiate between whether sex steroids or gonadotropins might modulate brain metal ion concentrations. Unlike other aging mammals, there was no increase in plasma luteinizing hormone (LH) and follicle-stimulating hormone (FSH) concentrations following estropause, suggesting sufficient residual production of estrogens and inhibins by the follicle depleted ovary of the mouse to suppress pituitary LH/FSH production. Castration on the other hand induced significant increases in circulating LH and FSH. Modulation of plasma sex steroid and gonadotropin levels did not significantly alter the concentrations of brain metals tested (Fe, Zn, Cu, Mn, Co, Ni, Al, Li), although there was a tendency for a decrease in all brain metals following ovariectomy (low estrogens and progesterone, high gonadotropins), a response that was reversed with leuprolide acetate treatment (low sex steroids, low gonadotropins). Brain Cu concentration was the only metal correlated with plasma LH (-0.37, n = 30, p< 0.05) and FSH (-0.42, n = 29, p< 0.01). This study demonstrates that sex hormones do not markedly alter brain metal ion homeostasis, unlike previously reported studies of circulating metal ion homeostasis. The role of gonadotropins in regulating metal ion homeostasis does however warrant further study.